Legal Challenges in Managing Social Conflicts in the Educational Environment - Elpina, Elpina (Indo-MathEdu Intellectuals Journal, 2024)
Education plays a crucial role in shaping a just and civilized society. However, the educational environment is not always free from social conflicts. This research aims to analyze the legal challenges in managing social conflicts in the community environment through the perspective of Law Number 20 Year 2003 concerning the National Education System. The research method employed is a literature review using data from Google Scholar from 2020 to 2024. Search keywords include law, social conflict, and the educational environment. The data analysis technique used in this research is qualitative data analysis. The qualitative data analysis process involves several steps, such as organising the data, forming themes or patterns, and interpreting the findings from the scientific articles used. The study findings indicate that managing social conflicts in the educational environment, in accordance with Law Number 20 Year 2003 concerning the National Education System, poses a complex challenge that requires a deep understanding of the legal principles contained within it. These conflicts often stem from differences of opinion or perspectives among various parties involved in the educational environment and can affect the stability and quality of education. To address these challenges, an integrated approach and concrete steps involving various relevant parties such as capacity-building are necessary.